Solve by Substitution

y= -3/2x -4

y= -1/2x =1

\( \begin{cases}y= - \frac{3}{2}x -4 \\ y= - \frac{1 }{2}x +1 \end{cases}\\ \\\begin{cases}y= - \frac{3}{2}x -4 \\ - \frac{3}{2}x -4 = - \frac{1 }{2}x +1 \end{cases}\\ \\\begin{cases}y= - \frac{3}{2}x -4 \\ - \frac{3}{2}x +\frac{1 }{2}x=1+4 \end{cases}\\ \\ \begin{cases}y= - \frac{3}{2}x -4 \\ - \frac{2}{2}x=5 \end{cases} \)

\( \begin{cases}y= - \frac{3}{2}x -4 \\ - x=5/*(-1) \end{cases}\\ \\ \begin{cases}y= - \frac{3}{2}*(-5)-4 \\ x=-5 \end{cases}\\ \\ \begin{cases}y= \frac{15}{2}-4 \\ x=-5 \end{cases}\\ \\ \begin{cases}y= 7\frac{1}{2}-4 \\ x=-5 \end{cases}\\ \\ \begin{cases}y= 3\frac{1 }{2} \\ x=-5 \end{cases}\\ \\ \)


\( \left\{\begin{array}{ccc}y=-\frac{3}{2}x-4 \\ y=-\frac{1}{2}x+1\end{array}\right. \\\\-\frac{3}{2}x-4=-\frac{1}{2}x+1\ /\cdot2\\\\-3x-8=-x+2\\\\-3x+x=2+8\\\\-2x=10\ /:(-2)\\\\x=-5\\\\y=-\frac{1}{2}\cdot(-5)+1=2,5+1=3,5\\\\ \left\{\begin{array}{ccc}x=-5\\y=3,5\end{array}\right. \)


RELATED: